2008
DOI: 10.1111/j.1365-3156.2008.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender effects in self‐reported urinary schistosomiasis in Tanzania

Abstract: Summaryobjectives To characterize age-gender prevalence profiles of urinary schistosomiasis according to the questionnaire responses, compare the profiles to field survey data from selected regions, and determine if the profiles varied spatially throughout Tanzania.methods In 2004, a national school-based questionnaire survey for self-reported schistosomiasis and blood in urine (BIU) was conducted in all regions of mainland Tanzania, to assist targeted mass distribution of praziquantel. Field survey data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
3
15
1
Order By: Relevance
“…The lower prevalence of reported blood in urine and the poor performance of reported blood in urine in identifying infected individuals, especially among older girls, corroborate with previous studies (Red Urine Study Group 1995; Lengeler et al 2002; Clements et al 2008a). For instance, a survey among Tanzanian school children found that 28.2% of girls reported blood in urine compared with 48.6% of boys and that reported blood in urine had a sensitivity of 51.5% and a specificity of 79.2%, but sensitivity was significantly lower in girls than in boys (39.6% vs. 61.9%) (Guyatt et al 1999).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The lower prevalence of reported blood in urine and the poor performance of reported blood in urine in identifying infected individuals, especially among older girls, corroborate with previous studies (Red Urine Study Group 1995; Lengeler et al 2002; Clements et al 2008a). For instance, a survey among Tanzanian school children found that 28.2% of girls reported blood in urine compared with 48.6% of boys and that reported blood in urine had a sensitivity of 51.5% and a specificity of 79.2%, but sensitivity was significantly lower in girls than in boys (39.6% vs. 61.9%) (Guyatt et al 1999).…”
Section: Discussionsupporting
confidence: 88%
“…Also in Tanzania, a 2004 national questionnaire survey was administered to over 2.5 million children in 12 399 schools across the country (Clements et al 2008b). Analysis of differences of reported blood in urine by age and sex found that whilst the prevalence of S. haematobium increased with age among girls, the prevalence of reported blood in urine either flattened out or decreased, indicating the latter underestimated prevalence in older girls (Clements et al 2008a). It has been suggested that the onset of menses influences girls’ willingness to report blood in urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other investigations did not show any difference in the prevalence of schistosomiasis according to the sex (Dabo et al, 2011). It appears that the prevalence of S. haematobium changes following the season and would be higher the raining season because of ecoclimatic conditions promoting parasite transmission (Clements et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve our objective, we adopted the proposition of Moestue et al [10] that the information given by students in a questionnaire is diagnostically reliable, so long as any under-or over-reporting is systematic and consistent, it could be used to identify schools where a health problem is common and where curative or preventive measures could be effectively directed. This notion has been well studied and validated for urinary schistosomiasis [16]- [18].…”
Section: Introductionmentioning
confidence: 99%